Procedures for application of the extended dosing after antitumor drug clinical trials - Yang, Feng; Heng, Jianfu; Liu, Yi; Tang, Qi; Li, Kunyan (Zhong nan da xue xue bao. Journal of Central South University. Yi xue ban, 2023)
New drug clinical trials have been considered as a positive way for treating cancer by cancer patients and doctors, and the extended dosing is a special way for patients' withdrawal from antitumor clinical trials to obtain investigational new drugs. However, neither the regulations of expanded dosing nor the detail documents for expanded dosing have been officially published in China. At present, expanded dosing of investigational drugs is still at the exploratory stage in various medical institutions, and a complete management system has not been established to meet patients' urgent needs for drug use. Based on the practical experience of extended dosing in Hunan Cancer Hospital, this paper preliminarily explored the application procedures and ethical review requirements of extended dosing for subjects in antitumor clinical trials. It is necessary to clarify the responsibilities of all patients in the procedure and establish a patient-medical institution-sponsor joint application system. In the process of ethical review, it is recommended that all parties fully consider the risks and benefits of extended dosing for patients, and then the ethics committee makes a comprehensive assessment to decide whether to approve extended dosing.